On strictly convex and strictly 2-convex 2-normed spaces II - C.-S. Lin (International Journal of Mathematics and Mathematical Sciences)
In this paper a new duality mapping is defined, and it is our object to show that there is a similarity among these three types of characterizations of a strictly convex 2-normed space. This enables us to obtain more new results along each of two types of characterizations. We shall also investigate a strictly 2-convex 2-normed space in terms of the above two different types.